Red yeast rice prepared from thai glutinous rice the antioxidant activities - Em On Chairote (2018)
Red yeast rice which is a product of solid fermentation was prepared from several kinds of Thai glutinous rice (Oryza sativa L.) cv. Korkor 6 (RD6), Kam (Kam) and Sanpatong1 (SPT1). Monascus purpureus CMU001 isolated from available Chinese red yeast rice was used as the fermentation starter. The analysis for the presence of antioxidant activity in red yeast rice was carried out by studying antioxidant capacity and β-carotene bleaching method (BCB). For the study on antioxidant activities of each kind of red yeast rice prepared, the ethanol extract from ground red yeast rice was used. Red yeast rice prepared from Oryza sativa L. cv. RD6 with the addition of soy bean milk for 3 weeks of cultivation had the darker red color. The shapes and the texture of the red yeast rice grains of glutinous rice appeared to be better. The highest antioxidant activity was obtained in red yeast rice of 3 weeks old from SPT1 and RD6 with the addition of soybean milk. The antioxidant capacity and the IC 50 of BCB methods were found to be 0.53 mg gallic acid equivalent (GAE) / ml and 0.09 mg/ml for both RD6 and SPT1 respectively. This result is concurrent to the production of darker red pigments.